Durability properties of multiple-blended binder concretes incorporating thermally activated alum sludge ash. (10th March 2019) - Owaid, Haider M.; Hamid, R.; Taha, M.R.
Highlights: Binary and ternary blended binders (BBB, TBB) include activated alum sludge ash (AASA). BBB concrete incorporating 15% AASA provided adequate durability properties. Durability properties of BBB concrete declined at 20% AASA replacement. TBB are more durable than BBB concretes at the same AASA replacement levels. Abstract: Binary and ternary blended binder (BBB and TBB, respectively) concretes are prepared by incorporating thermally activated alum sludge ash (AASA), silica fume (SF), ground granulated blast furnace slag (GGBS) and palm oil fuel ash (POFA) as partial cement replacement. Concrete mixtures were prepared with a water/binder ratio and total binder content of 0.30 and 493 kg/m 3, respectively. The evaluated durability performances of the multiple blended binder concretes included water absorption, porosity, initial surface absorption, sorptivity and sulfate and chloride resistance (immersed in 5% sodium sulfate (Na2 SO4 ), 5% sodium chloride (NaCl) solutions and water for 90 and 180 days). The results indicated that the BBB with 15% AASA cement replacement demonstrated superior durability performance compared with the control and 20% AASA concretes. A higher replacement level of 20% AASA did not improve inner core durability but improved surface durability characteristics. All TBB concretes performed better than the BBB concretes with AASA at the same replacement levels.